Nasal Polyps in Children: The Early Origins of a Challenging Adulthood Condition - Maria E. Di Cicco; Francesca Bizzoco; Elena Morelli; Veronica Seccia; Vincenzo Ragazzo; Diego G. Peroni; Pasquale Comberiati (MDPI AG, 2021)
Nasal polyps (NPs) are benign inflammatory masses causing chronic nasal obstruction, usually associated with underlying chronic rhinosinusitis (CRS), which are rarely reported in childhood. The interest in NPs has recently increased due to new therapeutic options, namely biological agents, such as dupilumab, and an update of the European position paper on this topic was released in 2020, providing a detailed classification for these lesions and also discussing diagnostic and therapeutic approaches also in children. In childhood, NPs usually represent red flags for systemic diseases, such as cystic fibrosis and immunodeficiencies. This review outlines the recent data on NPs in childhood, focusing on predisposing factors for CRS as well as on the potential endotypes in this particular age group, for which further studies are required in order to better clarify their pathogenesis and to identify molecular biomarkers that could help achieve more personalized treatments.